Investigation of growth-induced strain in monolayer MoS2 grown by chemical vapor deposition - Duesberg, Georg (My University, 2020)
Two-dimensional materials such as transitional metal dichalcogenides exhibit unique optical and electrical properties. Here we report on the varying optical properties of CVD grown MoS2 monolayer flakes with different shapes. In particular, it is observed that the perimeter and the central region of the flakes have non-uniform photoluminescence (PL) energy and intensity. We quantified these effects systematically and propose that thermally induced strain during growth is the origin. The strain relaxation after transfer of the MoS2 flakes supports this explanation. Detailed investigations of the spatial distribution of the PL energy reveal that depending on the shape of the MoS2 flakes, the width of the strain field is different. Thus, our results help to elucidate the fundamental mechanisms responsible for the differences in PL and Raman signals between the perimeter region and the center region of monolayer MoS2 and suggest that the induced strain plays an important role in the growth of monolayer materials.
Keywords: Chemical vapor deposition; Raman spectroscopy; Photoluminescence (PL); Strain; 2D materials; Monolayer 2D materials; MoS2; Transition metal dichalcogenides